Optimally sequencing semantic search predicts creativity - Olivier Toubia; Jonah Berger (PLoS ONE, 2026)
Creativity is a fundamental human activity which drives progress and innovation. Extant research has documented the link between creative performance and the efficient navigation of semantic space during the creative process, but we argue that an important aspect of efficiency has been overlooked: the optimal sequence of concepts retrieved. We develop a simple cognitive test, the Shortest Semantic Path Task, and an associated automatic measure (circuitousness), which capture this insight. Five initial validation studies demonstrate that this novel measure predicts creativity above and beyond existing measures, providing a more complete picture of creative performance. The psychometric properties of the specific instruments tested also reveal opportunities to develop more robust and consistent instruments to measure optimal sequencing in semantic search.